PEMBELAJARAN MUFRADAT BAHASA ARAB MELALUI PENERAPAN METODE DRILL - Baiq Tuhfatul Unsi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Abstract: The lack of students ability to master vocabulary caused by vocabulary mastery strategies that have not been effective and are not so strengthened in the teaching and learning process. In addition, also because of the lack of students who have an Arabic dictionary to Indonesia, conversely Indonesian to Arabic. This makes it difficult for students to explore the meaning of words. All students only rely on the vocabulary in the book and the rest students ask the teacher about the meaning of each difficult word. This requirement makes students less creative in developing their ability to collaborate vocabulary into other words that have different meanings because the source of information is only for teachers and LKS books. Introducing vocabulary alone is not enough to complete Arabic lessons, but by training students continuously, by means of repetition to facilitate the vocabulary that has been learned, after learning students who are drilled to translate the text that has been learned and translated in correct sentences, both in the form of speech and writing. So, in learning Arabic through this mufrodat drill method students are required to be more active and make students successful during the learning process.